Kausalitas Antara Pertumbuhan Ekonomi Dan Kemiskinan Di Provinsi Nusa Tenggara Timur Tahun 2002 – 2015 - Yuniarti Reny Renggo (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2017)
This study attempts to explain the causality relationship between economic growth and poverty in East Nusa Tenggara Province from 2002 to 2015. The data used is time series data analyzed using Granger Causality analysis tool. It is found that the economic growth is in the stationary state, while poverty is not. It is then differentiated at the first level (1st difference). Economic growth and poverty East Nusa Tenggara Province has a cointegration relationship and direct causal relationship where economic growth affects poverty. The result of Vector Error Corection Model (VECM) test shows that economic growth has a positive and significant impact on poverty in East Nusa Tenggara province, that 1% increase of economic growth can increase poverty by 1.855720. It is due to the diverse natural resources possessed by each area in East Nusa Tenggara, which the government should take into account when making policies in efforts to reduce poverty.